Analisis Produksi Kelapa Sawit Indonesia: Pendekatan Mikro dan Makro Ekonomi - Fevriera, Sotya; Devi, Fhrista Safara (JURNAL TRANSFORMATIF UNKRISWINA SUMBA, 2023)
As the biggest producer in the world, trend of Indonesia palm oil production keeps increasing. Therefore, palm oil industry is favorite in Indonesia’s plantation sector and agriculture export. Besides having contribution on Indonesia GDP, palm oil industry also absorbs many labors. The objective of this research is to study the effects of micro and macro economics variables on the total palm oil production, crude palm oil and kernel palm oil. Using time series data 1986-2020 and non linear multiple regression model estimated using ordinary least square method, this research found that area, palm oil export and exchange rate has a positive significant effect, inflation rate and interest rate has a negative significant effect whereas palm oil import has no significant effect on the production of total palm ol, crude palm oil and kernel palm oil. Hence, besides maintaining the stability of exchange rate, inflation rate and the interest rate fluctuation, the government have to put some efforts to develop researches to increase the productivity of palm oil area.